CRITICAL ANALYSIS OF EMERGENCY MEDICAL SERVICE SPECIALIST TRAINING IN ADDRESSING COMPETENCY GAPS AND INDUSTRY DEMANDS - Dhafer Fahad Mohammed Alsagoor, Nasser Faraj Mohammad Almareh, Abdulaziz Ali Mohammed Alyami, Alhussain Ibrahim Alqurayshah, Ali Mohammed Alyami, Ali Nasser Hamad Al Murdif, Ali Faisal Ali Alshareif, Nasser Hadi Ali Al Harshan,; Zabnallah Hassan Hamad Alkorbi (Chelonian Research Foundation, 2022)
This critical evaluation explores the formation of EMS professionals encompassing EMTs, radiological tech specialists, nursing specialists, lab techs, and dental assistants. The discrimination of gaps and the alignment of the training process with industrial demands are the constituent roles in improving the only care level dispensed by the EMS specialists. The significance of this study in achieving the objectives lies in the fact that it helps identify the areas of medicine within the training program that need further improvement to enhance the emergency medical response to various disease conditions. Through the discussion and analysis of specific operating methods and curriculum, this study aspires to improve the preparedness and efficiency of EMS professionals, which in turn can provide an enhanced level of patient care and increased efficiency of emergency medical services. Keywords: Emergency Medical Service Specialist, Training, Competency Gaps, Industry Demands, EMS Training Programs